PENGEMBANGAN MEDIA PEMBELAJARAN PREZI UNTUK KEMAMPUAN MEMAHAMI MATERI ISI DAN PESAN CERITA DONGENG MATA PELAJARAN BAHASA INDONESIA KELAS III - Tantri Widyastuti; Sukarir Nuryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning media is one of the important elements in the learning process. The use of learning media that is integrated with today's technology can facilitate the delivery of material to students more effectively. One of the interactive learning media is prezi media. The use of prezi-based media provides a new breakthrough in the delivery of material in the learning process. The purpose of this study was to determine the development (Research and Development) of prezi media modified from the R & D model from Bong and Gall. The methods used in collecting data are observation, interviews, documentation and tests. The research instrument is a questionnaire and test questions. The data analysis technique used data normality test, paired t test and N-gain test. The results showed that after going through the product validation stage by material experts obtained a score of 90.9% and by media experts obtained a score of 85.4% with a very feasible category. The effectiveness of the media was also tested by calculating the results of the initial test scores and the final test using a paired t-test obtained the average difference in the ability and learning outcomes of students before and after applying Prezi-based learning media. It is concluded that learning media using prezi is able to improve students' ability to understand fairy tale material and can convey fairy tale messages in Indonesian language learning content.